Exploring Student Acceptance and Perceptions of AI-Assisted PowerPoint Creation - Georgiev, Svetoslav; Tinsley, Joseph (African Journal of Inter/Multidisciplinary Studies, 2024)
Generative AI (GenAI) has had a disruptive effect on teaching and learning in Higher Education contexts. This paper addresses the need to examine students’ perceptions and acceptance of teacher GenAI usage in real world classroom settings. Using a qualitative research design, we explore the student acceptance and perceptions of AI-assisted learning materials (i.e., presentation slides generated by Microsoft PowerPoint Designer). The study draws its sample from one of the top transnational universities in China. Two rounds of focus group interviews with a total of 11 final-year undergraduate students majoring in Supply Chain Management were conducted in November 2023 in which students were asked to evaluate teacher PowerPoint slides created using AI assistance. Our analysis reveals that while students have a favourable opinion of instructor usage of AI-assisted PowerPoint slides, they are well-aware of the challenges and limitations of GenAI for PowerPoint creation and have substantial concerns with reference to the presentation slides’ design. Specifically, students expressed substantial concerns regarding AI-assisted PowerPoint content including structure, consistency between text and images, and even text font, size, and colour. This study contributes practical insights into the use of AI-assisted learning resources and the support needed for teachers and students to utilise these tools efficiently and in a way, which creates value.